Lack of effect of Lactobacillus rhamnosus GG and Bifidobacterium lactis Bb12 on beta-cell function in children with newly diagnosed type 1 diabetes: a randomised controlled trial - Hania Szajewska; Agnieszka Szypowska; Lidia Groele; Mieczysław Szalecki; Jolanta Świderska; Marta Wysocka-Mincewicz; Agnieszka Ochocińska; Anna Stelmaszczyk-Emmel; Urszula Demkow (BMJ Open Diabetes Research & Care, 2021)
Introduction The gut microbiota may be relevant in the development of type 1 diabetes (T1D). We examined the effects of Lactobacillus rhamnosus GG and Bifidobacterium lactis Bb12 on beta-cell function in children with newly diagnosed T1D.Research design and methods Children aged 8–17 years with newly (within 60 days) diagnosed T1D were enrolled in a double-blind, randomised controlled trial in which they received L. rhamnosus GG and B. lactis Bb12 at a dose of 109 colony-forming units or placebo, orally, once daily, for 6 months. The follow-up was for 12 months. The primary outcome measure was the area under the curve (AUC) of the C-peptide level during 2-hour responses to a mixed meal.Results Ninety-six children were randomised (probiotics, n=48; placebo n=48; median age 12.3 years). Eighty-eight (92%) completed the 6-month intervention, and 87 (91%) completed the follow-up at 12 months. There was no significant difference between the study groups for the AUC of the C-peptide level. For the secondary outcomes at 6 months, there were no differences between the study groups. At 12 months, with one exception, there also were no significant differences between the groups. Compared with the placebo group, there was a significantly increased number of subjects with thyroid autoimmunity in the probiotic group. However, at baseline, there was also a higher frequency of thyroid autoimmunity in the probiotic group. There were no cases of severe hypoglycemia or ketoacidosis in any of the groups. No adverse events related to the study products were reported.Conclusions L. rhamnosus GG and B. lactis Bb12, as administered in this study, had no significant effect in maintaining the residual pancreatic beta-cell function in children with newly diagnosed T1D. It remains unclear which probiotics, if any, alone or in combination, are potentially the most useful for management of T1D.Trial registration number NCT03032354.